Impacto del riesgo crediticio en la cartera de crédito en la coac p.a.i.s. ltda. - Pucuna Guanolema, Franklin Geovanny (2025)
Credit risk management emerges as an essential element in credit union loan portfolio management, as seen in the case of Cooperativa de Ahorro y Crédito COAC P.A.I.S. Ltda. Available research highlights that effective management of this risk is key to enhancing the quality of the loan portfolio, safeguarding its stability and recovery, and adapting quickly to financial market fluctuations. That is why the objective of this research is focused on evaluating credit risk and its influence on profitability in the Cooperativas de Ahorro y Crédito COAC P.A.I.S. Ltda. A qualitative research design has been implemented, including the review of documents. Among the main results is that it presents an average delinquency level of 7.83%, indicating certain variability in the capacity of borrowers to meet their financial obligations. This delinquency has a moderate negative correlation with return on equity (ROE) and return on assets (ROA), suggesting that an increase in delinquency tends to decrease the profitability of the cooperative. In conclusion, it shows strengths in terms of operational efficiency and management capacity, but there are significant challenges related to credit risk that affect its profitability. It is critical that the credit union implement effective risk management strategies and improve its operational efficiency to mitigate the negative impacts of credit risk and improve its long-term profitability.